2011
DOI: 10.1164/rccm.201106-1130oc
|View full text |Cite
|
Sign up to set email alerts
|

Altered MicroRNA Processing in Heritable Pulmonary Arterial Hypertension

Abstract: Rationale: Heritable pulmonary arterial hypertension (HPAH) is primarily caused by mutations of the bone morphogenetic protein (BMP) type-II receptor (BMPR2). Recent identification of mutations in the downstream mediator Smad-8 (gene, SMAD9) was surprising, because loss of Smad-8 function in canonical BMP signaling is largely compensated by Smad-1 and -5. We therefore hypothesized that noncanonical pathways may play an important role in PAH. Objectives: To determine whether HPAH mutations disrupt noncanonical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 37 publications
5
109
0
Order By: Relevance
“…Additionally, all glassware and plastics used for cell culture were opened in a sterile work environment. This protocol is detailed to give investigators the ability to study more reliably the role of pulmonary endothelial cells in lung vascular diseases (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, all glassware and plastics used for cell culture were opened in a sterile work environment. This protocol is detailed to give investigators the ability to study more reliably the role of pulmonary endothelial cells in lung vascular diseases (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Methodsmentioning
confidence: 99%
“…This group also demonstrated that the role of miR-204 and NFAT in PAH may be mediated by the DNA damage/ PARP-1 signaling pathway (59). Drake et al reported that heritable pulmonary arterial hypertension (HPAP)-associated mutation engender a primary defect in noncanonical miR processing, where bone morphogenetic protein (BMP) signaling is partially maintained (60). Smad-8 is responsible for this miR pathway.…”
Section: Epigeneticsmentioning
confidence: 99%
“…To date, over 200 distinct mutations have been identified in nearly 300 individuals, with nonsense point mutations accounting for approximately 29% overall (3,6). Less commonly, mutations are found in other BMP pathway genes: activin receptor-like kinase 1 (gene symbol, ACVRL1), endoglin (ENG), or Smad8 (gene symbol, SMAD9) (9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…There are also several Smad4-independent functions, including post-transcriptional up-regulation of a subset of microRNAs (miRs) (17,18). Recently, we showed that, in cells from the explant lungs of patients with HPAH, mutations in BMPR2 or SMAD9 abrogate this BMP-mediated miR induction (16). Two of the affected miRs, miR-21 and miR-27a, are growth suppressive in pulmonary vascular cells.…”
mentioning
confidence: 99%